2016
DOI: 10.1093/cercor/bhw145
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Amygdala–Hippocampal Connectivity and Multi-Voxel Correlation Structures During Awake Rest After Fear Learning Predicts Long-Term Expression of Fear

Abstract: After encoding, memories undergo a process of consolidation that determines long-term retention. For conditioned fear, animal models postulate that consolidation involves reactivations of neuronal assemblies supporting fear learning during postlearning "offline" periods. However, no human studies to date have investigated such processes, particularly in relation to long-term expression of fear. We tested 24 participants using functional MRI on 2 consecutive days in a fear conditioning paradigm involving 1 habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 87 publications
6
79
3
Order By: Relevance
“…Rather, our study was designed to determine whether, and how, encoding and reinstatement of verbal associations may be differently modulated by disgust and fear regardless of overall negative valence and arousal. Above all, we do not imply that AMY is not involved in fear processing [71][72][73] or that PHC cannot be involved in associative memory of different emotion categories 63 . However, we surmise that fear and disgust might recruit partly distinct emotion appraisal components that activate different kind of associations in memory and thus recruit partly distinct neural systems holding such associations.…”
Section: Possible Explanations Of Distinct Brain Mechanismscontrasting
confidence: 71%
“…Rather, our study was designed to determine whether, and how, encoding and reinstatement of verbal associations may be differently modulated by disgust and fear regardless of overall negative valence and arousal. Above all, we do not imply that AMY is not involved in fear processing [71][72][73] or that PHC cannot be involved in associative memory of different emotion categories 63 . However, we surmise that fear and disgust might recruit partly distinct emotion appraisal components that activate different kind of associations in memory and thus recruit partly distinct neural systems holding such associations.…”
Section: Possible Explanations Of Distinct Brain Mechanismscontrasting
confidence: 71%
“…Behavioural and neuroscientific studies primarily in adults identified a host of different factors why interindividual differences emerge. Such factors are, among others, working memory capacity (e.g., the function to maintain a limited amount of information in the presence of distraction; Unsworth & Engle, ), emotional arousal (McGaugh, ), memory strategies (Unsworth, ), knowledge (Ericsson & Kintsch, ), degree of learning (Loftus, ; Slamecka & McElree, ) (Unsworth, ; Unsworth, Spillers, & Brewer, ), and neurophysiological features like the amount of baseline dopamine release (Cools & D'Esposito, ), fibre density (Kanai & Rees, ), and associated differences in neural activity and communication between brain areas relevant for encoding and consolidation of the information (Ben‐Yakov, Dudai, & Mayford, ; Fell & Axmacher, ; Hermans et al ., ; Shrager, Kirwan, & Squire, ; Tambini et al ., ; Wislowska, Heib, Griessenberger, Hoedlmoser, & Schabus, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trait anxiety was also associated with increasing coupling between the basolateral amygdala and anterior midcingulate cortex, supporting fear expression following extinction learning (Belleau et al, 2018). Remarkably, the rsFC of the amygdala might reflect distinctions in neural networks at the fear extinction stage in healthy participants (Feng et al, 2015) and might even predict the long-term expression of fear (Hermans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%